The work environment, critical incidents, debriefing and psychological functioning—a study of trade union members in Sweden - Söndergaard, Hans Peter (SJWEH Supplements, 2008)
' ' OBJECTIVES ': 'This study explored the associations between critical incidents, the psychosocial work environment, debriefing, and poor psychological health, including posttraumatic stress disorder (PTSD), among shop attendants. ' ' METHODS ': 'Questionnaires were administered to members of the Swedish trade union and to persons who had had brief treatment after a robbery. ' ' RESULTS ': 'Of the respondents, 6.6% reported robbery in their workplace. Those who were repeatedly exposed to robberies and scored above the cut-off for PTSD comprised 14.2–16.4% of the total number of PTSD cases. The workers exposed to a robbery felt less safe at work, without differing from others regarding other measures of psychosocial factors, namely, social support, influence, and job strain. The participants with PTSD reported significantly worse social support at work, but did not differ as to influence or demand–control. Debriefing (yes, no) had no statistical relationship with the prevalence of PTSD among robbery victims, but, in the whole group, including other traumatic events, debriefing showed a weak, albeit significant association with self-rated psychological function. The debriefed (after any negative work- or nonwork-related event) participants did not differ as regards symptoms of PTSD, but they reported less depression and better psychological functioning, even after adjustment for social support at work. A long sick leave after a robbery was associated with poor support from managers and colleagues. ' ' CONCLUSIONS ': 'Social support, including support from managers, was associated with few symptoms, good psychological function, and shorter sick leave. People with PTSD have poorer general work conditions and social support, but similar influence or demand–control at work.
Keywords: anxiety; critical incident; debriefing; depression; positive state of mind; posttraumatic stress disorder; psychological functioning; robbery; state of mind; Sweden; trade union; trade union member; work environment